Non-Burning Bricks with Natural Materials Environmentally Friendly - Adhi Aqwam; Asryadin Asryadin; Muhammad Ichwanul Muslimin; Rizka Khairunnisa; Hetti Koes Endang; Rosita Rosita; Fahrul Annas; Hasan Hasan; Muhammad Rahadian (Jurnal Penelitian Pendidikan IPA, 2023)
The city of Bima is an area that produces quite a lot of bricks with favorable natural conditions, most of the area consists of rice fields and has a soil texture suitable for making bricks. Red brick is the most widely produced type of brick with a total of 20,000 bricks per month and its use has a negative impact on the environment because it produces carbon dioxide (CO2) emissions which pollute the air and contribute to the greenhouse effect which causes global warming, also as a result of burning bricks. . Based on this, researchers are trying to conduct research related to building materials in Bima City in the form of brick innovations with more environmentally friendly basic materials. The research was carried out using a true experiment and cross sectional approach using conventional bricks as a standard for quality comparison. Descriptive analysis was chosen as the method of analysis in this study. From the results of brick quality tests, all brick formulas met the requirements for water content (<15%), four of the six formulas met the compressive strength requirements based on SNI. The average compressive strength of the four formulas is >5 MPa and meets the Indonesian national brick breaking strength standard (SNI-0021-78). The most significant advantage seen from brick products without burning is the lower water content than conventional bricks and is more environmentally friendly because it uses natural materials and is obtained at competitive prices